Vitamin D [25(OH)D] metabolites and epimers in obese subject: Interaction and correlations with adverse metabolic health risk factors - Gariballa, Salah; Shah, Iltaf; Yasin, Javed; Alessa, Awad (The Journal of steroid biochemistry and molecular biology, 2022)
•Higher BMI and lower vitamin D may increase metabolic risk factors.•Viatmin D metabolites may affect measurement and function of total vitamin D.•We examined the associations between vitamin D metabolites, increasing BMI and metabolic risk factors.•No evidence to support a role for vitamin D metabolites in mediating the effect of BMI on metabolic risk factors. Although both vitamin D deficiency and obesity are highly prevalent in the UAE, the role of vitamin D metabolites in mediating obesity-related adverse health effects is not clear. We aimed to assess the role of vitamin D metabolites as potential mediators in the association between obesity, inflammation and metabolic risk factors. 277 participants who were part of a randomized controlled trial had their assessment that included clinical, anthropometric and physical activity data at baseline and at 6 months. Blood and urine samples were taken for measurements of serum 25(OH)D, 25(OH)D metabolites including 25(OH)D3), 25(OH)D2), 1,25(OH)2D3, 3-Epi-D3), metabolic and inflammatory markers and related biochemical variables. Multiple regression analysis used to assess the role of 25(OH)D metabolites in mediating the effect of increasing body mass index (BMI) on inflammation and metabolic risk factors. Overall, 277 participants with complete 6 months follow up with a mean (±SD) age of 41 ± 12 and 204 (74%) female were included in the study. Blood pressure, inflammatory, metabolic and lipid profile markers significantly increased in overweight and obese subjects compared to subjects with normal BMI both at baseline and at 6 months (p < 0.05). 25(OH)D revealed significant association with age, gender, HbA1c and type 2 diabetes (p < 0.05). No statistically significant changes in any of 25(OH)D metabolites assessed. Multivariate analysis revealed significant and independent associations between BMI and important inflammatory and metabolic risk factors (p < 0.05). No similar association observed with 25(OH)D metabolites. Although we found significant association between 25(OH)D and prevalence of type 2 diabetes, we found no evidence however to support a role of 25(OH)D metabolites in mediating the effect of BMI on inflammatory or metabolic risk factors.